Environmental fate of 2, 4-dinitroanisole (DNAN) and its reduced products. (January 2015) - Hawari, J.; Monteil-Rivera, F.; Perreault, N.N.; Halasz, A.; Paquet, L.; Radovic-Hrapovic, Z.; Deschamps, S.; Thiboutot, S.; Ampleman, G.
Highlights: DNAN undergoes regioselective reduction at the o -NO2 under abiotic and biotic conditions. Physicochemical parameters ( Sw, p K a, log K ow, Kd ) are provided for DNAN and its amine products. Physicochemical behavior depends on type and position of substituent(s) on the aromatic ring. Amine products of DNAN irreversibly bind to soil under oxic conditions. Abstract: Several defense departments intend to replace 2, 4, 6-trinitrotoluene (TNT) in munitions formulations by the less sensitive 2, 4-dinitroanisole (DNAN). To help understand environmental behavior and ecological risk associated with DNAN we investigated its key initial abiotic and biotic reaction routes and determined relevant physicochemical parameters (p K a, log K ow, aqueous solubility ( Sw ), partition coefficient ( Kd )) for the chemical and its products. Reduction of DNAN with either zero valent iron or bacteria regioselectively produced 2-amino-4-nitroanisole (2-ANAN) which, under strict anaerobic conditions, gave 2, 4-diaminoanisole (DAAN). Hydrolysis under environmental conditions was insignificant whereas photolysis gave photodegradable intermediates 2-hydroxy-4-nitroanisole and 2, 4-dinitrophenol. Physicochemical properties of DNAN and its amino products drastically depended on the type and position of substituent(s) on the aromatic ring. Sw followed the order (TNT < DNAN < 2-ANAN < 4-ANAN < DAAN) whereas log K ow followed the order (DAAN < 4-ANAN < 2-ANAN < DNAN < TNT). In soil, successive replacement of NO2 by NH2 in DNAN enhanced irreversible sorption and reduced bioavailability under oxic conditions. Although DNAN is more soluble than TNT, its lower hydrophobicity and its tendency to form aminoderivatives that sorb irreversibly to soil contribute to make it less toxic than the traditional explosive TNT.